Methods for Transition Toward Computer Assisted Cognitive Examination - Jurica, P.; Valenzi, S.; Struzik, Z. R.; Cichocki, A. (Methods of Information in Medicine, 2015)
Introduction: We present a software framework which enables the extension of current methods for the assessment of cognitive fitness using recent technological advances.Background: Screening for cognitive impairment is becoming more important as the world’s population grows older. Current methods could be enhanced by use of computers. Introduction of new methods to clinics requires basic tools for collection and communication of collected data.Objectives: To develop tools that, with minimal interference, offer new opportunities for the enhancement of the current interview based cognitive examinations.Methods: We suggest methods and discuss process by which established cognitive tests can be adapted for data collection through digitization by pen enabled tablets. We discuss a number of methods for evaluation of collected data, which promise to increase the resolution and objectivity of the common scoring strategy based on visual inspection. By involving computers in the roles of both instructing and scoring, we aim to increase the precision and reproducibility of cognitive examination.Results: The tools provided in Python framework CogExTools available at http://bsp.brain.riken.jp/cogextools/ enable the design, application and evaluation of screening tests for assessment of cognitive impairment. The toolbox is a research platform; it represents a foundation for further collaborative development by the wider research community and enthusiasts. It is free to download and use, and open-source.Conclusion: We introduce a set of open-source tools that facilitate the design and development of new cognitive tests for modern technology. We provide these tools in order to enable the adaptation of technology for cognitive examination in clinical settings. The tools provide the first step in a possible transition toward standardized mental state examination using computers.
Keywords: Cognitive test; cognitive impairment; health information exchange; health information database; open-source; software framework; Python programming language; computer-aided diagnosis